An input-driven approach to generate class diagram and its empirical evaluation - Mohamed Salleh F.H. (2023)
This paper presents an approach for generating Unified Modeling Language (UML) class diagram. The objective of the project is to assist users in generating class diagram in a systematic way, with less dependent to the developers' skill. The approach consists of a number of steps or instructions to be executed by users. Executing the steps requires the user to enter inputs that will then generate half-completed class diagram. Step-by-step approaches are presented to show how the candidate of classes, attributes and relationships between classes are captured. The proposed approach is presented using a case study of ATM system. Testing was conducted to assess the effectiveness of the proposed approach. Analysis and discussion of the testing results are discussed in a few last sections of this paper. The development of the system is underway. 2011 Springer-Verlag.